Palestine in Muhammadiyah Narrative: Movement, Aid, and Moral Diplomacy 2021-2025 - Rahmawati Elantri, Aulia; Surwandono, Surwandono (Review of International Relations (Jurnal Kajian Ilmu Hubungan Internasional), 2025)
This article examines Muhammadiyah’s involvement in supporting the struggle of humanity and Palestinian nationality based on 100 news uploaded on the muhammadiyah.or.id from 2021 to 2025. Data was analyzed with a qualitative approach through clustering into several coding categories, namely year, economic, social, educational, and political assistance. The results of the study show that Muhammadiyah’s commitment to the Palestinian issue is very high, consistent, and sustainable. The aid distributed includes economic support in the form of humanitarian fundraising, social assistance such as logistics and medicine deliveries, and educational contributions through the provision of scholarships and the construction of educational facilities for Palestinian children. In addition, Muhammadiyah is also active in moral and political diplomacy by voicing Palestinian justice and independence in various national and international forums. The big idea developed by Muhammadiyah is to build solidarity of the people based on universal humanity and global justice, by placing the Palestinian issue as a moral test for modern civilization. This commitment shows the strategic role of Muhammadiyah as a transnational Islamic movement that is not only active domestically, but also responsive to global dynamics that touch on human and ummah values.